An Analytical Study on the Direction and Implementation of Arabic as a Foreign Language Instruction at the Ma’had of IAIN Kerinci - Rangga Prasetya; Widiya Yul; Riko Andrian (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to analyze the direction and implementation of Arabic language instruction as a foreign language within the environment of Ma’had IAIN Kerinci. Employing a qualitative case study approach, the research explores various aspects of language learning, including goal formulation, teaching methods, student motivation, and curriculum relevance. The findings reveal that the direction of Arabic instruction at Ma’had IAIN Kerinci is significantly influenced by the alignment between learning objectives, curriculum design, methodological approaches, and students’ internal factors. The primary discovery highlights that the instructional direction, which has not been explicitly formulated, contributes to a lack of cohesion between curriculum content, teaching methods, and communicative competence goals. The study underscores the importance of a well-defined instructional direction as a central element that influences the effectiveness of communicative-based pedagogical approaches. Furthermore, it suggests that curriculum reform emphasizing functional and applied language skills is essential. Innovative teaching methods also play a vital role in enhancing students’ active participation and emotional engagement. Additionally, this study identifies two major motivational poles among students—academic and religious—which shape their learning orientation and imply the necessity for a dual-responsive instructional design. These findings indicate that instructional direction is not merely a pedagogical concept but a strategic foundation that determines the quality and relevance of Arabic language education as a foreign language.